Whole-body autoradiography and allied tracer techniques in distribution and elimination studies of some organic solvents: benzene, toluene, xylene, styrene, methylene chloride, chloroform, carbon tetrachloride and trichloroethylene. - Bergman, Kerstin (Scandinavian Journal of Work, Environment & Health, 1979)
Whole-body autoradiography has been used to study the distribution and fate of 14C-labeled benzene, toluene, xylene, styrene, methylene chloride, chloroform, carbon tetrachloride and trichloroethylene in mice after inhalational exposure. Total radioactivity, including the volatile part of the solvents were registered by autoradiography of dried, evaporated tape-fastened sections. In addition, dried, evaporated tape-fastened sections were extracted with water, trichloroacetic acid and a series of organic solvents and autoradiographed to register organs where metabolites were firmly bound. In another facet of the study, the quantitative elimination of the solvents and their metabolites via various routes was investigated. The expiration of unchanged solvents was subject to mathematical and computerized compartmental pharmacokinetic analysis. All solvents were rapidly taken up in fatty and nervous tissues where they were retained for different periods of time largely dependent on their fat solubility. Unexpectedly long retention times were noted for the chlorinated solvents, particularly for chloroforn, which showed a specific long-term retention in the cerebellum, meninges and spinal nerves, indicating interactions with specific nervous tissue receptors. Solvent metabolites appeared rapidly in several organs, mainly the liver and kidney, and were excreted both via urine and bile. Toluene and xylene metabolites were completely extractable whereas firmly bound metabolites were registered after inhalation of benzene, styrene and all chlorinated solvents, notably in the liver and kidney but also in the bronchi of the lung. Three-compartment pharmacokinetics were observed for the majority of the solvents selected for study although a two-compartment model was found to fit the elimination rate curves for styrene, methylene chloride and chloroform in the exhaled air. The fat solubility of the solvents was found to influence their pharmacokinetics since lower rate constants were generally obtained for the expiration of more fat soluble solvents.
Keywords: allied tracer technique; benzene; carbon tetrachloride; chloroform; distribution; elimination; methylene chloride; organic solvent; styrene; toluene; trichloroethylene; whole-body autoradiography; xylene